Black Market of Democracy: The Anomaly of Buying Political Party Recommendation Letters of Regional Leader Candidates in Indonesia - Rofiq, Rofiq (Unnes Political Science Journal, 2023)
This article is arranged based on qualitative research results with a case study approach in one of the major political parties in Indonesia. This research found that the practice of recruiting regional leader candidates by political parties is not open and undemocratic. There are fraudulent actions and anomalies in the recruitment of regional leader candidates. The practice of buying and selling recommendation letters from the central party is real and occurs. Even though it is carried out secretly by some party elites, the perpetrators seem to be in a black market, as their existence is carried out tactically and cautiously. The selection of regional leader candidates conducted by political parties is followed by all groups, both from outside the party and cadres of the party itself. In reality it is those who have adequate political resources, especially from a financial perspective, who will get party approval.